Mitochondrial Control Region and microsatellite analyses on harbour porpoise (Phocoena phocoena) unravel population differentiation in the Baltic Sea and adjacent waters - Annika Wiemann; Liselotte W. Andersen; Per Berggren; Ursula Siebert; Harald Benke; Jonas Teilmann; Christina Lockyer; Iwona Pawliczka; Krzysztof Skora; Anna Roos; Thomas Lyrholm; Kirsten B. Paulus; et al. (Conservation Genetics, 2010)
The population status of the harbour porpoise (Phocoena phocoena) in the Baltic area has been a continuous matter of debate. Here we present the by far most comprehensive genetic population structure assessment to date for this region, both with regard to geographic coverage and sample size: 497 porpoise samples from North Sea, Skagerrak, Kattegat, Belt Sea, and Inner Baltic Sea were sequenced at the mitochondrial Control Region and 305 of these specimens were typed at 15 polymorphic microsatellite loci. Samples were stratified according to sample type (stranding vs. by-caught), sex, and season (breeding vs. non-breeding season). Our data provide ample evidence for a population split between the Skagerrak and the Belt Sea, with a transition zone in the Kattegat area. Among other measures, this was particularly visible in significant frequency shifts of the most abundant mitochondrial haplotypes. A particular haplotype almost absent in the North Sea was the most abundant in Belt Sea and Inner Baltic Sea. Microsatellites yielded a similar pattern (i.e., turnover in occurrence of clusters identified by STRUCTURE). Moreover, a highly significant association between microsatellite assignment and unlinked mitochondrial haplotypes further indicates a split between North Sea and Baltic porpoises. For the Inner Baltic Sea, we consistently recovered a small, but significant separation from the Belt Sea population. Despite recent arguments that separation should exceed a predefined threshold before populations shall be managed separately, we argue in favour of precautionary acknowledging the Inner Baltic porpoises as a separate management unit, which should receive particular attention, as it is threatened by various factors, in particular local fishery measures. © Springer Science+Business Media B.V. 2009.